Analisis Kepuasan Terhadap Konsumen Waroeng Steak And Shake Kota Malang - Karunia Setyowati Suroto; Jatmiko Setiaji; Anung Prasetyo Nugroho; Ariani Trisna Murti (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2026)
This study aims to analyze and empirically prove the effect of product quality, price, service quality, and convenience on customer satisfaction at Waroeng Steak and Shake in Malang City. The main focus is to identify the most contributing determinants in shaping positive customer experiences amidst intense competition in the culinary industry. A quantitative approach with a survey method was employed , using purposive sampling of 100 active customers. This sample size meets the statistical power criteria for regression analysis in the context of consumer behavior research. Data were analyzed using multiple linear regression. The results indicate that partially and simultaneously, product quality, price, service quality, and convenience have positive and significant effects on customer satisfaction. The findings reveal that service quality is the most dominant factor in increasing customer satisfaction, followed by convenience, price, and product quality. The coefficient of determination (R2) of 70.3% shows that this model has high predictive ability in explaining variations in customer satisfaction.